2020
DOI: 10.1080/21691401.2020.1730391
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of doxofylline against lipopolysaccharides (LPS)-induced activation of NLRP3 inflammasome is mediated by SIRT1 in human pulmonary bronchial epithelial cells

Abstract: Liu (2020) The protective effect of doxofylline against lipopolysaccharides (LPS)-induced activation of NLRP3 inflammasome is mediated by SIRT1 in human pulmonary bronchial epithelial cells, Artificial Cells,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 20 publications
0
13
2
Order By: Relevance
“…In this study, it was found that the SIRT1 improved these disorders by inhibiting the NLRP3 inflammasome [36]. Another study found that the Doxofylline inhibited NLRP3 inflammasome via SIRT1 and thus prevented inflammation in lung epithelial cells [37]. Studies have shown that the GD15 is able to prevent acute pulmonary inflammation by increasing the expression of SIRT1 in the inflammation-caused lung injury of rats following the NLRP3 inflammasome activation [38].…”
Section: Effect Of Quercetin On Sirt1 As Anti-inflammatory Factor and Nlrp3 Inflammasome Inhibitormentioning
confidence: 71%
“…In this study, it was found that the SIRT1 improved these disorders by inhibiting the NLRP3 inflammasome [36]. Another study found that the Doxofylline inhibited NLRP3 inflammasome via SIRT1 and thus prevented inflammation in lung epithelial cells [37]. Studies have shown that the GD15 is able to prevent acute pulmonary inflammation by increasing the expression of SIRT1 in the inflammation-caused lung injury of rats following the NLRP3 inflammasome activation [38].…”
Section: Effect Of Quercetin On Sirt1 As Anti-inflammatory Factor and Nlrp3 Inflammasome Inhibitormentioning
confidence: 71%
“…Lipopolysaccharide (LPS) is usually applied in animal model to induce systemic inflammation 46 , 47 and also applied in leukocytes or other cells to induce inflammatory reactions or cell damage 48 , 49 . However, LPS is seldom applied in neutrophils to examine transendothelial migration.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous animal models of sepsis (LPS or CLP) have demonstrated common abnormalities: increased level of ROS, decreased antioxidant capacity, and mitochondrial oxidative damage [14,15,74]. LPS-triggered generation of mitochondrial superoxide measured usually with the fluorogenic dye MitoSOX was demonstrated in different cell types, such as microglia [75,76], muscle myoblasts [23], gingival fibroblasts [17], human pulmonary bronchial epithelial cells [77], macrophages [78], and others. In addition, the decline in antioxidative enzymes and glutathione content caused by LPS contributes to the impairment of endogenous antioxidant defense and the subsequent increase in mtROS generation [79][80][81][82][83].…”
Section: Lps Triggers Mtros Generationmentioning
confidence: 99%